2003
DOI: 10.1016/j.asieco.2003.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth in the Philippines: theory and evidence

Abstract: Note: UPSE Discussion Papers are preliminary versions circulated privately to elicit critical comments. They are protected by the Copyright Law (PD No. 49) and not for quotation or reprinting without prior approval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Despite Malaysia's massive educational expansion, no significant increase in the rate of return to schooling was found for the period 1984–97 (Milanovic 2006). A recent study of Philippines’ data over the 1980–2001 period concluded that only population growth has a significant impact on economic growth; education had a positive but insignificant impact (Canlas 2003). 21 For Taiwan, its ability to export has been the lead actor in its per capita GNP growth (Fan and Fan 2004).…”
Section: Education and Economic Growth In East Asiamentioning
confidence: 99%
“…Despite Malaysia's massive educational expansion, no significant increase in the rate of return to schooling was found for the period 1984–97 (Milanovic 2006). A recent study of Philippines’ data over the 1980–2001 period concluded that only population growth has a significant impact on economic growth; education had a positive but insignificant impact (Canlas 2003). 21 For Taiwan, its ability to export has been the lead actor in its per capita GNP growth (Fan and Fan 2004).…”
Section: Education and Economic Growth In East Asiamentioning
confidence: 99%
“…Other studies show that below a certain threshold level of family income, married women work even if they have only low levels of education. However, if family income is above that threshold, married women with considerable levels of education may opt not to work because their spouses can already support the family (Canlas & Encarnacion 1976;Encarnacion 1973). This hypothesis is consistent with the traditional sexual division of labor, with husbands as main economic providers and wives as homemakers and providers of child care.…”
Section: Candidate Specificationsmentioning
confidence: 99%